Counselling by general dental practitioners for coronectomy before referral – is it always appropriate?. (6th September 2020) - Beaumont, I.; Richards, J.A.; Coyle, M.J.; Finley, B.; Beech, A.N.
Abstract: Aims: For the general dental practitioner (GDP) coronectomy may be a treatment option that is discussed with a patient prior to referral to a specialist in primary or secondary care for management of problematic mandibular third molars. The purpose of this study was to examine the variance between coronectomy prescription between GDPs compared to specialist clinicians when assessing cases for coronectomy using plain view radiographs. Methods: An online survey was completed by 50 GDPs across the UK. This survey had also been completed by 25 specialist oral and maxillofacial or oral surgery clinicians of varying levels of experience from six different units across the UK and the Republic of Ireland. Results: Results were compared and, whilst agreement between GDPs was higher in coronectomies prescribed, there was a significantly larger number of coronectomies prescribed in the GDP group. Conclusions: The increased number of coronectomies prescribed by the GDP group compared to the specialist group could reflect a lack of experience in the regular assessment of mandibular third molars or a clinician being more aware of the litigious climate of dentistry when based in primary dental care.